2021
DOI: 10.3390/pharmaceutics13101671
|View full text |Cite
|
Sign up to set email alerts
|

AS1411 Aptamer Linked to DNA Nanostructures Diverts Its Traffic Inside Cancer Cells and Improves Its Therapeutic Efficacy

Abstract: The nucleolin-binding G-quadruplex AS1411 aptamer has been widely used for cancer therapy and diagnosis and linked to nanoparticles for its selective targeting activity. We applied a computational and experimental integrated approach to study the effect of engineering AS1411 aptamer on an octahedral truncated DNA nanocage to obtain a nanostructure able to combine selective cancer-targeting and anti-tumor activity. The nanocages functionalized with one aptamer molecule (Apt-NC) displayed high stability in serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 50 publications
3
22
0
Order By: Relevance
“…The comparative studies of Apt‐NCs with free aptamer showed that Apt‐NCs have high serum stability and a 200‐fold increase in anti‐tumor activity. The results show that aptamer is constrained by the nanocage to a more defined conformation which is probably related to the different intracellular localization and enhanced therapeutic effect of AS1411 aptamer [81] …”
Section: Aptamers As Therapeuticsmentioning
confidence: 97%
See 1 more Smart Citation
“…The comparative studies of Apt‐NCs with free aptamer showed that Apt‐NCs have high serum stability and a 200‐fold increase in anti‐tumor activity. The results show that aptamer is constrained by the nanocage to a more defined conformation which is probably related to the different intracellular localization and enhanced therapeutic effect of AS1411 aptamer [81] …”
Section: Aptamers As Therapeuticsmentioning
confidence: 97%
“…The results show that aptamer is constrained by the nanocage to a more defined conformation which is probably related to the different intracellular localization and enhanced therapeutic effect of AS1411 aptamer. [81] Zhang et al developed an AS1411 aptamer containing ProteolysisTargetingChimeras (PROTACs) against breast cancer cells. PROTACs are small molecules with heterobifunctional properties and they are highly efficient for protein degradation.…”
Section: Aptamers As Therapeuticsmentioning
confidence: 99%
“…However, as evidenced previously, breast-cancer-cell-specific aptamer AS1411 can be conjugated with a PROTAC molecule (as inspired by antibody–drug conjugates) as a delivery means to selectively target cancer cells over normal cells [ 21 ]; this constitutes the third layer of precision targeting. One could use structurally modified AS1411 as an alternative [ 96 , 97 , 98 , 99 , 100 , 101 , 102 ], because AS1411 was withdrawn from clinical trials [ 103 ]. The main reason for the withdrawal of AS1411 from clinical trials was its insufficient anti-cancer activity; meanwhile, its safety issue was found to be good [ 44 ].…”
Section: Perspectivesmentioning
confidence: 99%
“…Aptamers are oligonucleotide sequences with a length of around 20-80 bases, including short single-strand DNA (ssDNA) or RNA molecules, first introduced in the 1990s (Debra L. Robertson, 1990;Doug Irvine, 1991), that bind to their specific targets with high affinity and specificity thanks to their stable three-dimensional folding. Due to their lower cost, smaller size (about 10-fold smaller), and easier modification compared to antibodies, aptamers have become ideal recognition candidates for diagnostic and therapeutic agents, targeted drug delivery systems (Jéssica Lopes-Nunes et al, 2020), biosensing probe (Giulia Vindigni et al, 2021;Fuze Jiang et al, 2022;Tong Mo et al, 2022), etc. Aptamers are usually developed via systematic evolution of ligands by exponential enrichment (SELEX), while AS1411 is the first non-SELEX anticancer aptamer discovered serendipitously by Paula J.…”
Section: Introductionmentioning
confidence: 99%